2008
DOI: 10.1002/sia.2890
|View full text |Cite
|
Sign up to set email alerts
|

Surface characteristic of poly(p‐phenylene terephthalamide) fibers with oxygen plasma treatment

Abstract: Oxygen plasma is widely employed for modification of polymer surfaces. Plasma treatment process is a convenient procedure that is also environmentally friendly. This study reports the effects of oxygen plasma treatment on the surface properties of poly(p-phenylene terephthalamide) (PPTA) fibers. The surface characteristics before and after oxygen plasma treatment were analyzed by XPS, atomic force microscopy (AFM) and dynamic contact angle analysis (DCAA). It was found that oxygen plasma treatment introduced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…It seems that there exists an optimum plasma treatment time under discharge power of 200 W for aramid fiber surfaces, which is in accordance with the results derived from the XPS analysis and AFM observation in Ref. [4].…”
Section: Influence Of Oxygen Plasma Treatment On Composite Interfaciasupporting
confidence: 87%
See 1 more Smart Citation
“…It seems that there exists an optimum plasma treatment time under discharge power of 200 W for aramid fiber surfaces, which is in accordance with the results derived from the XPS analysis and AFM observation in Ref. [4].…”
Section: Influence Of Oxygen Plasma Treatment On Composite Interfaciasupporting
confidence: 87%
“…[3] In our previous work, it has been reported that oxygen plasma treatment is an effective method to introduce some new polar groups (O-C O) to the fiber surface, increase the fiber surface roughness, and improve the fiber surface wettability. [4] All of these would be a benefit for improving the interfacial adhesion in a composite system. [5] Moreover, the modified fiber surface by oxygen plasma treatment may suffer from aging after being stored a period of time in air at room temperature, leading to a change in the fiber surface chemical composition and degradation of surface wettability.…”
Section: Introductionmentioning
confidence: 99%
“…This is because larger contact area can contribute to a higher degree of the mechanical interlocking between wire bond interfaces [48]. Thus, bond pads having cleaner surface after argon plasma treatment are able to enlarge the contact area and improve the interfacial adhesion of wire bond significantly.…”
Section: Wire Bond Interfacial Adhesion Analysis Resultsmentioning
confidence: 99%
“…In particular, the ratios of each peak area were altered compared with those of the untreated CFRP. The ratios of the area of the C C peak, C O peak, C O and O C O peaks were 50.7%, 30.1%, 9.4%, and 7.4%, respectively [16]. Consequently, the oxygen plasma treatment changed the chemical components on the CFRP surface and the newly formed functional groups improved the surface polarity and its hydrophilicity [16][17].…”
Section: Afm and Xps Analysismentioning
confidence: 97%